2018
DOI: 10.32910/ep.69.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Indeks pouzdanja potrošača kao navješćujući indikator promjena prometa u trgovini na malo

Abstract: Cilj rada je empirijski ispitati postojanje povezanosti prometa u trgovini na malo i Pokazatelja pouzdanja potrošača na razini Europske unije i na razini euro područja. Pokazatelj pouzdanja potrošača (engl. Consumer Confi dence Indicator, CCI) je kompozitni pokazatelj ocjena i očekivanja potrošača u zemljama EU i EA. U istraživanju se ispituje mogućnost predviđanja smjera promjene prometa u trgovini na malo, a ne i intenziteta te promjene. Pri tome se ispituje povezanost predviđenih (po promjenama CCI-a) i ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The authors found a weakening of a correlation between the indicators and a reference series (industrial production) leading them to a conclusion that these indicators should undergo moderations for improving their predictive features. Čižmešija and Orlović (2018) empirically examined the relationship between turnover in retail trade and the Consumer confidence indicator on the aggregate level of the European Union (EU) and on the aggregate level of the Euro zone (EA) for the period 2005-2017. The possibility of forecasting the direction of changes in retail trade turnover was examined and not the intensity of change.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors found a weakening of a correlation between the indicators and a reference series (industrial production) leading them to a conclusion that these indicators should undergo moderations for improving their predictive features. Čižmešija and Orlović (2018) empirically examined the relationship between turnover in retail trade and the Consumer confidence indicator on the aggregate level of the European Union (EU) and on the aggregate level of the Euro zone (EA) for the period 2005-2017. The possibility of forecasting the direction of changes in retail trade turnover was examined and not the intensity of change.…”
Section: Literature Reviewmentioning
confidence: 99%